Evidence for long noncoding RNA GAS5 up-regulationin patients with Klinefelter syndrome - Michele Salemi; Rossella Cannarella; Rosita A. Condorelli; Laura Cimino; Federico Ridolfo; Giorgio Giurato; Corrado Romano; Sandro La Vignera; Aldo E. Calogero (BMC, 2019)
Abstract Background Klinefelter syndrome (KS) is characterized by the presence of at least one supernumerary X chromosome. KS typical symptoms include tall stature, gynecomastia, hypogonadism and azoospermia. KS patients show a higher risk of developing metabolic and cardiovascular diseases, inflammatory and autoimmune disorders, osteoporosis and cancer. Long non-coding RNA (lncRNA) growth arrest-specific 5 (GAS5) has been shown to be involved in several biologic processes, including inflammatory and autoimmune diseases, vascular endothelial cells apoptosis and atherosclerosis, as well as cellular growth and proliferation, cellular development and cell-to-cell signaling and interaction. The lncRNA GAS5 expression profile in KS patients has never been evaluated so far. Methods To accomplish this, GAS5 mRNA levels were evaluated by Next Generation Sequencing (NGS) technology and qRT-PCR assay in 10 patients with KS and 10 age-matched controls. Results NGS results showed a significantly lncRNAGAS5up-regulation by 5.171-fold in patients with KS. Theresults of qRT-PCR confirmed the NGS data. Conclusions These findings showed the occurrence of lncRNA GAS5 over-expression in KS patients. Whether this lncRNA is involved in the pathogenesis of inflammation and autoimmune diseases, atherogenesis or germ cell depletion in KS patients is not known. Further studies are needed.